Exposure to teachers smoking and adolescent smoking behaviour: analysis of cross sectional data from Denmark. Issue 3 (1st September 2002) - Poulsen, L H; Osler, M; Roberts, C; Due, P; Damsgaard, M T; Holstein, B E
Abstract : Objective: To determine whether adolescent smoking behaviour is associated with their perceived exposure to teachers or other pupils smoking at school, after adjustment for exposure to smoking at home, in school, and best friends smoking. Design: Logistic regression analysis of cross sectional data from students in Denmark. Subjects: 1515 grade 9 students (mean age 15.8) from 90 classes in 48 Danish schools. Outcome measure: Self reported smoking behaviour; daily smoking and heavy smoking, defined as those smoking more than 20 cigarettes per week. Results: Of the students in this study, 62% of boys and 60% of girls reported being exposed to teachers smoking outdoors on the school premises. The proportion of boys and girls reporting to have been exposed to teachers smoking inside the school building were 86% and 88%, respectively. Furthermore, 91% of boys and 92% of girls reported that they had seen other students smoking outdoors on the school premises. Adolescents' perceived exposure to teachers smoking outdoors on the school premises was significantly associated with daily smoking, having adjusted for sex, exposure to teachers smoking indoors at school and pupils smoking outdoors at school, as well as the smoking behaviour of mother, father, and best friend (odds ratio (OR) 1.8, 95% confidence interval 1.2 to 2.8). Adolescents' perceived exposure to teachers smoking inside the school building was not associated with daily smoking (OR 0.9, 95% CI 0.5 to 1.6) and perceived exposure to pupils smoking outdoors was not associated with daily smoking (adjusted OR 1.5, 95% CI 0.5 to 4.4). There were similar findings with heavy smoking as the outcome variable. Conclusions: Teachers smoking during school hours is associated with adolescent smoking. This finding has implications for future tobacco prevention strategies in schools in many countries with liberal smoking policies where it might provide support for those working to establish smokefree schools.